Strategi Pengembangan Teknologi Pengolahan Sagu pada UMKM di Provinsi Riau - Gevisioner, Gevisioner; Mutiara, Candra Sari (Department of Agribusiness, Halu Oleo University, 2020)
The community and industry have been developing sago products. However, the downstream industrial development of sago products carried out by the community is still very limited, both in terms of type and quality. The aim of this study was to formulate strategies and policies for the development of technology for downstream sago products, especially sago noodles. The study was conducted in the Meranti Islands District in 2019, with a sample of 40 sago noodle micro, small and medium enterprises (MSMEs). Data collection was carried out by means of surveys and focus group discussions (FGD). Data analysis using SWOT analysis. The results of the research found that the majority of sago processing technology was still traditional and semi-modern and 87.5% of the sago noodle product quality was not good. Efforts to organize the production space according to product hygienic sanitation standards and improve sago noodle product packaging technology are the right strategies to improve the quality of sago noodles. Therefore the policy of developing sago noodle downstream product technology is implemented by Building supporting facilities for the smooth running of the sago noodle business, such as providing clean and proper water facilities for processing sago noodles, Providing socialization, and improving the quality of human resources regarding quality and sago noodle packaging.